Assessment of PRRSV and PCV2 seroprevalence and antigen prevalence in minipigs at laboratory-animal production facilities (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Pigs are used in various biomedical research fields because of their anatomical and physiological similarities to humans. While farm pigs are raised outdoors for several months, minipigs are typically raised in indoor barrier facilities for several years. Although numerous studies have investigated the prevalence of major pathogens, including porcine reproductive and respiratory syndrome virus (PRRSV) and porcine circovirus type 2 (PCV2), in farm pigs, similar studies targeting minipigs are lacking. Materials and Methods: We imported 57 minipigs to our institution from three experimental animal production facilities and immediately assessed the serological and antigenic prevalence of PRRSV and PCV2. Results: PRRSV and PCV2 had seroprevalences of 80.7% and 94.7%, respectively, with 0% antigen positivity rates for PRRSV types 1 and 2 and high-pathogenic PRRSV and PCV2. Two factors could account for the high seroprevalence rates: the majority of individuals may have been vaccinated despite official claims from the origin facilities or exposed to PRRSV and PCV2. Preventing microbial infections is crucial for obtaining accurate and reproducible results. Conclusion: As the first investigation of microbial prevalence in minipigs, our findings indicate that minipigs raised in barrier facilities are not necessarily free from vaccines or infections. These results will significantly enhance the credibility of future biomedical research.J. Adv. Vet. Anim. Res., 11(4): 1017–1022, December 2024http://doi.org/10.5455/javar.2024.k852